2021
DOI: 10.1186/s42397-021-00087-3
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping and domestication analysis to dissect genetic improvement process of upland cotton yield-related traits in China

Abstract: Background Cotton fiber yield is a complex trait, which can be influenced by multiple agronomic traits. Unravelling the genetic basis of cotton fiber yield-related traits contributes to genetic improvement of cotton. Results In this study, 503 upland cotton varieties covering the four breeding stages (BS1–BS4, 1911–2011) in China were used for association mapping and domestication analysis. One hundred and forty SSR markers significantly associated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The variance, normality statistical analyses, and basic statistics, including extreme values, mean value, standard deviation, coefficient of variation, and statistics for the correlation between traits were performed using SPSS v22.0 software (IBM Corp., Armonk, NY, USA). Correlation analyses and boxplots between environments were drawn using R software (Guo et al, 2021).…”
Section: Phenotype Investigation and Statistical Analysismentioning
confidence: 99%
“…The variance, normality statistical analyses, and basic statistics, including extreme values, mean value, standard deviation, coefficient of variation, and statistics for the correlation between traits were performed using SPSS v22.0 software (IBM Corp., Armonk, NY, USA). Correlation analyses and boxplots between environments were drawn using R software (Guo et al, 2021).…”
Section: Phenotype Investigation and Statistical Analysismentioning
confidence: 99%
“…The variance, normality statistical analyses and basic statistics including extreme values, mean value, standard deviation, variable coe cient, and the statistics for the correlation between traits were performed by using SPSS software 22.0. Correlation analysis and boxplot between environments were drawn using R software (Guo et al 2021).…”
Section: Phenotype Analysismentioning
confidence: 99%
“…The first association mapping study in cotton focusing on fiber quality was reported in G. arboretum ( Kantartzi and Stewart, 2008 ). Subsequently, association mapping has been extensively applied in upland cotton to investigate crucial economic traits, including fiber quality ( Abdurakhmonov et al., 2008 ; Nie et al., 2016 ; Liu et al., 2020 ; Song et al., 2021 ), seed oil content ( Liu G. et al., 2015 ; Yuan et al., 2018 ; Zhao et al., 2019 ), fiber yield ( Ademe et al., 2017 ; Sun et al., 2018 ; GUO et al., 2021 ; Niu et al., 2023 ), and biotic and abiotic stresses ( Fang et al., 2010 ; Bardak et al., 2021 ; Xu et al., 2021 ; Zhang et al., 2021 ; Zhao et al., 2021 ), as well as those associated with epistasis and environmental interactions ( Jia et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%